A Randomized Defence of Virus Throttling - Mowbray, Miranda; Ananthanarayanan, Ganesh; Joseph, Anthony (2008)
This paper gives a simple example of a defense against a worm attack which is a randomized combination of pure strategies, and which is superior to all of the pure strategies that it combines. Although it was developed to defend against an attack on virus throttling in a specific network device, both the attack and the defense are rather generic, and may be applicable to other areas.
HP Laboratories Tech Report, HPL-2008-135